2022
DOI: 10.1021/acsestengg.1c00417
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Surfactant-Mediated Coagulation for Enhanced Removal of Toxic Metal–Organic Complexes: Performance, Mechanism, and Validation

Abstract: Toxic metal ions tend to complex with coexisting organic ligands in contaminated waters, challenging their efficient removal via traditional processes such as adsorption, coagulation, or precipitation. In this study, we demonstrate a proof-of-concept strategy for the removal of metal–organic complexes using cationic surfactants as the coagulant. Using cetyltrimethylammonium bromide (CTAB) as the model one, such a simple strategy is applicable for efficient water decontamination from various metals [Cr­(III), N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The rate constant for the cathode modified by OTAB was 0.2158 h –1 , which was 9.38, 22.48, and 38.54 times higher than CTAB (0.0230 h –1 ), TTAB (0.0096 h –1 ), and DTAB (0.0056 h –1 ), respectively. The positive correlation between the removal efficiency and the alkyl chain lengths of the surfactants was associated with the more hydrophobic nature of longer-chain surfactants. Through stronger hydrophobic interactions, more PFMeUPA molecules were adsorbed onto the cathode surface and degraded by the electrons. Without surfactant modification, the defluorination efficiency was less than 20% (Figure e).…”
Section: Resultsmentioning
confidence: 99%
“…The rate constant for the cathode modified by OTAB was 0.2158 h –1 , which was 9.38, 22.48, and 38.54 times higher than CTAB (0.0230 h –1 ), TTAB (0.0096 h –1 ), and DTAB (0.0056 h –1 ), respectively. The positive correlation between the removal efficiency and the alkyl chain lengths of the surfactants was associated with the more hydrophobic nature of longer-chain surfactants. Through stronger hydrophobic interactions, more PFMeUPA molecules were adsorbed onto the cathode surface and degraded by the electrons. Without surfactant modification, the defluorination efficiency was less than 20% (Figure e).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, we recently reported that heavy metal complexes mixed with surfactants could form selfassemblies via electrostatic and hydrophobic interactions. 34 The self-assembly process is highly dependent on the charge of the terminal group and the length of the alkyl chain of surfactants. Inspiringly, in this study, 3-mercapto-1-propanesulfonic acid sodium salt (MPS) with a negative terminal group (−SO 3 − ) and a propane hydrophobic chain (C3) 35 and tributylhexadecylphosphonium bromide (THPB) with a positive terminal group (−P + (C 4 H 9 ) 3 ) and a cetyl hydrophobic chain (C16) 36 are selected as the surface modifiers of Au nanosensors, aiming to provide different hydrophobic and electrostatic interactions toward Ni(II) species.…”
Section: T H Imentioning
confidence: 99%
“…As reported, N -acetyl- l -cysteine (NAC) and adenosine monophosphate (AMP) have been employed to chelate Ni­(II) via the amino and phosphate groups, exhibiting extremely high selectivity toward Ni­(II) over other metal ions in alkaline conditions. Besides, we recently reported that heavy metal complexes mixed with surfactants could form self-assemblies via electrostatic and hydrophobic interactions . The self-assembly process is highly dependent on the charge of the terminal group and the length of the alkyl chain of surfactants.…”
Section: Introductionmentioning
confidence: 99%